2022
DOI: 10.1080/21655979.2021.2018092
|View full text |Cite
|
Sign up to set email alerts
|

LINC00472 suppresses oral squamous cell carcinoma growth by targeting miR-455-3p/ELF3 axis

Abstract: LINC00472 is reported to play a role in suppressing tumors in cancers such as lung cancer and hepatocellular carcinoma, among others. We made investigations into the effects of LINC00472 in oral squamous cell carcinoma (OSCC) progression to explore the underlying molecular mechanisms. By qRT-PCR, we assessed the LINC00472 expression in OSCC tissues and cells and performed functional analysis to investigate how LINC00472/miR-455-3p/ELF3 impacts OSCC cell proliferation, apoptosis, and cell cycle. The role that L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…They may function as cis-regulatory elements such as enhancers and silencers, or as transcribed non-coding RNA to exert regulatory functions [ 34 36 ]. For example, MIR647, MIR99AHG, and LINC00472, identified in our differentially methylated analysis, could regulate the progression of oral squamous cell carcinoma, prostate cancer, and lung adenocarcinoma by promoting cell proliferation, migration, epithelial-mesenchymal transition, and other processes [ 37 – 40 ]. Although some genes annotated by EM-seq DMRs currently have no research revealing their biological functions, it does not seem to affect their potential as candidate biomarkers for tumor diagnosis because base sequences have been detected.…”
Section: Discussionmentioning
confidence: 99%
“…They may function as cis-regulatory elements such as enhancers and silencers, or as transcribed non-coding RNA to exert regulatory functions [ 34 36 ]. For example, MIR647, MIR99AHG, and LINC00472, identified in our differentially methylated analysis, could regulate the progression of oral squamous cell carcinoma, prostate cancer, and lung adenocarcinoma by promoting cell proliferation, migration, epithelial-mesenchymal transition, and other processes [ 37 – 40 ]. Although some genes annotated by EM-seq DMRs currently have no research revealing their biological functions, it does not seem to affect their potential as candidate biomarkers for tumor diagnosis because base sequences have been detected.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that MiR-455-3p has varying impacts on the development of various malignancies. For instance, miR-455-3p expression was elevated in oral squamous cell carcinoma, and overexpression of miR-455-3p prevented the anticancer effects of LINC00472 [ 13 ]. In contrast, miR-455-3p prevented the progression of prostate cancer cells in vitro and in vivo [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-455-3p can interact with lncRNA to take part in the development of many tumors. By way of illustration, miR-455-3p sponged by LINC00472 could worsen the progression of oral squamous cell carcinoma [ 13 ]. Oppositely, miR-455-3p interacted with LINC00319 to suppress osteosarcoma progression [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, HCT-116 and HT-29 cells were incubated with luteolin (0, 10, 20, and 40 μM) in the presence or absence of 5 μM of cisplatin for 48 h. Subsequently, cells were cultivated with 10 μL of Annexin V in the dark for 15 min, followed by the addition of 10 µL of propidium iodide (PI) to the cell suspension. Finally, the apoptosis rate of the cells was detected using a FACScan flow cytometer (BD Biosciences, CA, USA) [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, after rinsing with PBS, the cells were re-suspended in 500 μL of buffer containing 10 μL of RNAse (Sigma) and 25 µL of PI (BD Biosciences) and incubated at room temperature for 30 min in the dark. The percentage of cells in different phases (G1, S, and G2) of the cell cycle was detected by flow cytometry (BD Biosciences, Franklin, NJ, USA) [ 28 , 30 ].…”
Section: Methodsmentioning
confidence: 99%